Reinvensi Islam multikultural - Halaqah Tarjih 2004 : Jakarta, Indonesia); Baidhawy, Zakiyuddin; Thoyibi, M. (Surakarta : Pusat Studi Budaya dan Perubahan Sosial, Universitas Muhammadiyah Surakarta, 2005)
Muhammadiyah, Islam, and multiculturalism in Indonesia; collection of articles
Keywords: Religious pluralism -- Islam; Multiculturalism -- Religious aspects -- Islam; Religious pluralism -- Indonesia; Multiculturalism -- Indonesia